2018
DOI: 10.1080/20008686.2018.1490135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofLeptospiraspp. and Seoul hantavirus in brown rats (Rattus norvegicus) in four regions in the Netherlands, 2011-2015

Abstract: Background:  Brown rats (Rattus norvegicus) may carry pathogens that can be a risk for public health. Brown rats in the Netherlands were tested for the zoonotic pathogens Leptospira spp. and Seoul hantavirus (SEOV), in order to obtain insight in their prevalence. Methods and results:  Cross-sectional studies were performed at four locations from 2011 to 2015. The rats were tested for Leptospira spp. using real-time PCR and/or culture resulting in a prevalence ranging between 33–57%. Testing for SEOV was done t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
(22 reference statements)
1
26
2
Order By: Relevance
“…In this way, they pose a serious threat for surface water contamination. Studies on pathogenic Leptospira from various countries in Europe on R. norvegicus show mean infection percentages between 21-57% (Aviat et al, 2009;Maas et al, 2018;Runge et al, 2013). Our research showed a lower infection percentage in the small mammals tested (5.3%) than the other published studies from European countries.…”
Section: Leptospira Spp Prevalence In Wild Small Mammalscontrasting
confidence: 59%
See 3 more Smart Citations
“…In this way, they pose a serious threat for surface water contamination. Studies on pathogenic Leptospira from various countries in Europe on R. norvegicus show mean infection percentages between 21-57% (Aviat et al, 2009;Maas et al, 2018;Runge et al, 2013). Our research showed a lower infection percentage in the small mammals tested (5.3%) than the other published studies from European countries.…”
Section: Leptospira Spp Prevalence In Wild Small Mammalscontrasting
confidence: 59%
“…A recent study from the Netherlands reported an infection range of 33-57% in brown rats (Maas et al, 2018). It is known that the infection rate amongst rats is highly variable in time and place (Kuiken, 1990;Kuiken, van Dijk, Terpstra, & Bokhout, 1991), which is also underpinned by the recent study in the Netherlands (Maas et al, 2018). We found a lower infection percentage in the small mammals tested (5.3%) than these European studies.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Rats are the main reservoir host of hantavirus and leptospirosis infection [3][4][5]. The transmission of hantavirus infection and leptospirosis is related to one's exposure with the rats and its feces [6].…”
Section: Introductionmentioning
confidence: 99%